Children as Agents of Change: Research Reflections on the Practice and Possibilities of Participatory Eco-justice Research - Crump, Holly; Jagger, Susan; Radakovic, Nenad; Matheson, Ian; Carlton, Chris (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
This article takes the form of a conversational text in which we as five adult educational researchers reflect on our varied and intersecting experiences in conducting eco-justice education research with elementary school students as co-researchers. Drawing on a theoretical and rhizomatic foundation of children’s rights, sociology of childhood, and eco-justice, we describe our engagement with a Grade 5/6 class on a participatory research project centered on vermicomposting. We situate ourselves within the action research spiral of ‘plan-act-reflect’ as we dialogue and think together about our experiences as co-researchers with students and look ahead to future opportunities to fully realize children’s rights and justice in environmental education and research. We center our discussion on three guiding questions: 1) What is eco-justice education and what might it look like within the context of participatory research with children? 2) How can adult researchers empower children’s autonomy and active citizenship in ecological research while engaging as co-researchers with them? 3) What are the strengths, challenges, and possibilities for children’s participation as eco-justice and climate action researchers? Our reflective text contributes to a body of knowledge around the meaningful engagement and empowerment of children in eco-justice and climate action explorations and activism.